Synergistic nano-tribological interaction between zinc dialkyldithiophosphate (ZDDP) and methyl oleate for biodiesel-fueled engines - Siti Hartini, Hamdan; Lee, Chiew Tin; Lee, Mei Bao; William Chong, Woei Fong; Chong, Cheng Tung; Suhaila, Mohd Sanip (Springer Nature, 2021)
: In biodiesel-fueled compression-ignition (CI) engines, dilution by unburned biodiesel has been found to have adverse effects on the boundary lubrication properties of additives in fully formulated engine lubricants. Such dilution of engine lubricants could be even more pronounced for CI engines running on higher blend concentrations of biodiesel. Given the nanoscopic nature of the interaction, this study seeks to determine the nano-tribological properties of an engine lubricant additive (e.g., zinc dialkyldithiophosphate (ZDDP)) when diluted with a fatty acid methyl ester (e.g., methyl oleate). Using lateral force microscopy (LFM) together with a fluid imaging technique, the lowest nanoscopic friction forces and coefficient of friction values (0.068–0.085) were measured for ZDDP when diluted with 70 vol% of methyl oleate. These values are also observed to be lower than those measured for neat ZDDP and neat methyl oleate, respectively, under similar conditions. Subsequently, interpreting the data with the Eyring thermal activation energy approach, it could then be elucidated that the lower frictional losses observed for the contact lubricated with this volumetric mixture are a result of the lower potential energy barrier and activation energy required to initiate sliding. These energy values are approximated to be 2.6% and 28.9% (respectively) lower than that of the contact lubricated with neat ZDDP. It was also found that the mixture, at this volumetric concentration, possesses the highest possible pressure activation energy (load-carrying capacity) along with the lowest possible shear activation energy (shearing), potentially indicating optimum tribological conditions for boundary lubrication. Thus, the findings of this study suggest that an optimum concentration threshold exists in which a synergistic nano-tribological interaction between additives and fatty acid methyl esters can be attained potentially reducing boundary frictional losses of lubricated conjunctions. Such findings could prove to be essential in effectively formulating synergistic additive concentrations for engine lubricants used in biodiesel-fueled CI engines.